Salinity tolerance of Passiflora tarminiana Coppens & Barney - Hurtado Salazar, Alejandro; Pereira da Silva, Danielle Fabíola; Ceballos-Aguirre, Nelson; Ocampo, John; Bruckner, Claudio Horst (Sociedad Colombiana de Ciencias Horticolas, 2018)
*Passiflora tarminiana* is a climbing glycophyte, native to the Andean region that has tolerance to salinity and moderate water stress. The aim of this study was to evaluate its capacity for sodium excretion as a possible strategy for salinity tolerance and the drought. Salt excretion and excreted ion concentrations were evaluated in plants grown for seven months under various levels of salinity [(NaCl) 2.5, 4.0, and 5.5 dS m^-1^ (25, 40 and 55 mM)] and moderate water stress (33 and 100% moisture in the substrate). The experiment design was completely randomized in a split-plot array, where the plot was determined by the percentage of water saturation (33% and 100%). The ubplot had saturation levels of salinity (EC: 2.5, 4.0, and 5.5 dS m^-1^), with five replicates. The experiment unit consisted of one plant. Salt crystals and structures of the leaf epidermis were evaluated. Salts were excreted in the adaxial leaf surface, possibly because of specialized salt secreting glands. Other structures, such as trichomes and papillae, were also observed, which are believed to also be involved in the salt tolerance of *P. tarminiana*.